HR Policy Development for a Construction and Supplies Company in Ligao City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
This construction and supplies firm fabricate and supply pre-cast beam and concrete post for road bridges and high level structures. The company supplies locally fabricated construction materials to construction companies in the Philippines. The company has around 200 workers where most of them are working in project sites. Review of the company’s policy may provide basis on additional ways to address the concerns of its workforce. The researchers conducted written and oral interview with the company president. The company’s consultant was also interviewed to gather information and also provided the company manual which for reference. Gathered information about the company’s current policies, procedures and programs were analyzed and compared to common effective processes of other companies in the same industry and with the labor law to come up with reliable recommendations. The researchers have identified possible recommendations for enhancement of the company’s programs and policies which includes provisions health insurance of employees, Anti-Age Discrimination Policy, Drug-Free Workplace, Care of Equipment and Facilities, Data Privacy Policy, Employee Self-Service System, Reimbursement, Enhancement of Online Recruitment, a Contractual Template for Fixed Term Employees, Personal Protective Equipment and hazardous materials, Training and Seminars, Rehire Process, Performance Evaluation Template, Consultative Management Style and Grievance Committee. These proposals are deemed beneficial to both employees and the firm and may be used for implementation or reference in enhancing their current policies.
Keywords: policy development, construction company, policies, procedures